TINGKAT KESUKAAN OTAK-OTAK IKAN DARI BAHAN BAKU JENIS DAGING IKAN YANG BERBEDA - -, Junianto -; Helisa, Nanda (Politeknik Kelautan dan Perikanan Pangandaran, 2025)
Research on the level of liking of fishcake from raw materials of different types of fish meat was conducted in May 2024. This study aims to determine the level of panelists' preference for the type of fish meat used to make otak-otak. Organoleptic data was processed using a non-parametric test in the form of the Friedman test and using the Bayes test for decision making. The organoleptic test on appearance resulted in an average score of 7.53 for snapper; 5.80 for tilapia; and 4.86 for skipjack. Organoleptic test on aroma resulted in an average score of 6.60 for snapper; 6.20 for tilapia; and 5.93 for skipjack. Organoleptic test on texture resulted in an average score of 6.73 for snapper; 5.26 for tilapia; and 4.60 for skipjack. The organoleptic test on flavor produced an average score of 7.13 for snapper; 6.73 for tilapia; and 5.26 for skipjack. The decision-making method using the Bayes test shows that taste is the most important criterion in this study with the highest criterion weight of 0.46 and snapper is the most preferred brain-brain with an alternative value of 7 and a priority value of 21.54.